Fuzzy-based Nutrient System for Chili Cultivation in Urban Area - C. Hairu; M. Hanafi; T.Z. Hang; S. Mashohor; W. F. F. Ilahi (IAES Indonesian Section, 2022)
The right level of nutrients is crucial for chilli cultivation as the crop requires different nutrient levels at different growth stages. The current fertiliser supply needs many human resources, which is time-consuming. Thus, an automatic nutrient controlling system giving the exact amount of fertiliser based on Fuzzy logic and IoT technology is proposed in this paper. The proposed system uses Hostinger platform to monitor water level, electrical conductivity (EC) and pH values in real-time. Fuzzy membership functions and rules decide the precise amount of nutrients to chilli plants based on the EC value and water level at each growth stage. The Fuzzy membership functions are designed according to the nutrients requirement in each chilli’s phenological stage. The proposed system results are compared with the traditional approach, where fertilisers are supplied manually every week. The experiment results showed that the proposed system could meet the precise and automatic fertiliser addition requirement, eliminate human intervention and ensure the plants grew well.